Metformin for endometrial hyperplasia (Review) - Clement, Naomi S.; Oliver, Thomas R.W.; Shiwani, Hunain; Sanner, Juliane R.F.; Mulvaney, Caroline A.; Atiomo, William (Cochrane Collaboration, 2017)
Background Endometrial cancer is one of the most common gynaecological cancers in the world. Rates of endometrial cancer are rising, in part because of rising obesity rates. Endometrial hyperplasia is a precancerous condition in women that can lead to endometrial cancer if left untreated. Endometrial hyperplasia occurs more commonly than endometrial cancer. Progesterone tablets currently used to treat women with endometrial hyperplasia are associated with adverse effects in up to 84% of women. The levonorgestrel intrauterine device (Mirena Coil, Bayer HealthCare Pharmaceuticals, Inc., Whippany, NJ, USA) may improve compliance, but it is invasive, is not acceptable to all women, and is associated with irregular vaginal bleeding in 82% of cases. Therefore, an alternative treatment for women with endometrial hyperplasia is needed. Metformin, a drug that is often used to treat people with diabetes, has been shown in some human studies to reverse endometrial hyperplasia. However, the effectiveness and safety of metformin for treatment of endometrial hyperplasia remain uncertain.